A case report of complete pancreatic lipomatosis - Satwik, Nuvvula; Koppad, Sanjay Nagappa; Nadipally, Srikar Rao (International Surgery Journal, 2021)
The pancreas is an exocrine and endocrine organ that is related to the stomach, duodenum, colon and spleen. Fatty degeneration of the pancreas is common with aging. The entire pancreas may be replaced by fat and the patient may have no clinical symptoms. We here presented a case of a 28 years old male known case of type 2 diabetes diagnosed 3 months back, who was admitted to our hospital for diffuse abdominal pain for the past 2 months, which was non-colicky in nature associated with nausea, anorexia, diarrhea and generalized weakness, no aggravating or relieving factors. With this scenario, he was investigated further for abdominal pain and found to have pancreatic lipomatosis.